2001
DOI: 10.1590/s0037-86822001000400007
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência da infecção pelo vírus da hepatite B (VHB) e delta (VHD) em sete grupos indígenas do Estado do Amazonas

Abstract: Resumo A infecção pelo VHB e VHD são importantes problemas de saúde na Amazônia. Este estudo avalia a prevalência da infecção por esses agentes em sete grupos indígenas do Estado do Amazonas. A taxa de infecção passada pelo VHB encontrada foi de 54,5% e a de portadores do AgHBs de 9,7%. Observa-se variação importante destes marcadores entre as aldeias, inclusive da mesma etnia. Não evidenciamos marcador de infecção aguda, os quatro AgHBe reativos eram todos Apurinã, da mesma aldeia, e três da mesma família. O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
22

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 13 publications
(2 reference statements)
2
21
0
22
Order By: Relevance
“…15,[22][23][24][25][26] In this study, it was possible to investigate the epidemiological aspects of HBV infection in the general populations of three rural communities on the Purus river basin, in the municipality of Lá brea, western Amazon, Brazil, using molecular epidemiology as a tool to interpret the distribution and transmission dynamics of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…15,[22][23][24][25][26] In this study, it was possible to investigate the epidemiological aspects of HBV infection in the general populations of three rural communities on the Purus river basin, in the municipality of Lá brea, western Amazon, Brazil, using molecular epidemiology as a tool to interpret the distribution and transmission dynamics of HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Among the indigenous population of the Western Amazon, serum epidemiological studies reported prevalence rates of chronic carriers above 20% 8,11 .…”
Section: Methodsmentioning
confidence: 99%
“…The Brazilian Amazon region is characterized as one of the regions of the world with a high occurrence of HBV-associated disease and its sequelae 8 . The State of Amazonas, the Brazilian Amazon, the Juruá, the Solimões, and the Purus…”
Section: Article/artigomentioning
confidence: 99%
“…A análise da seqüência do genoma do VHD revelou evidências da transmissão do VHD entre casais, sugerindo os autores deste estudo que a transmissão do VHD por via sexual possa ocorrer 50 . Mais recentemente, estudos realizados em sete grupos indígenas do Estado do Amazonas, sugerem que a transmissão sexual representa o mecanismo mais importante na disseminação do VHD na população 4 .…”
Section: B Aunclassified